1996
DOI: 10.2307/1511208
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities Definitions and Criteria Used by State Education Departments

Abstract: This article reports the results of a survey of the 51 state departments of education (including Washington, DC) regarding their definitions of learning disabilities, identification criteria, and operationalization procedures. A conceptual framework consisting of eight components was used in analyzing the definitions and identification criteria. Results show the continued effect of the 1977 federal definition and criteria while revealing variations in state definitions and criteria. For example, several state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…The stipulation of a severe discrepancy between achievement and IQ was retained in the Individuals with Disabilities Education Act (IDEA) amendments of 1997. The majority of state definitions have included a discrepancy criterion for many years (Frankenberger & Fronzaglio, 1991;Mercer, Jordan, Allsopp, & Mercer, 1996;Mercer, King-Sears, & Mercer, 1990), and 96% of states were continuing to use IQ-achievement discrepancy in their classification criteria as recently as 2002 (Reschly & Hosp, 2004). More than half of the states reported using standard scores, and 90% of those specified a discrepancy cutoff of 1 SD or greater (Frankenberger & Fronzaglio, 1991).…”
mentioning
confidence: 99%
“…The stipulation of a severe discrepancy between achievement and IQ was retained in the Individuals with Disabilities Education Act (IDEA) amendments of 1997. The majority of state definitions have included a discrepancy criterion for many years (Frankenberger & Fronzaglio, 1991;Mercer, Jordan, Allsopp, & Mercer, 1996;Mercer, King-Sears, & Mercer, 1990), and 96% of states were continuing to use IQ-achievement discrepancy in their classification criteria as recently as 2002 (Reschly & Hosp, 2004). More than half of the states reported using standard scores, and 90% of those specified a discrepancy cutoff of 1 SD or greater (Frankenberger & Fronzaglio, 1991).…”
mentioning
confidence: 99%
“…The term does not include children who have learning problems which are primarily the result of visual, hearing, or motor handicaps, of mental retardation, or emotional disturbance, or of environmental, cultural, or economic disadvantage. (USOE, 1977, p. 65083) Mercer, Hughes, and Mercer (1985) found that 72% of the states used the 1977 definition or a variation thereof-a trend that has persisted to the present time, as 71 % were found to use the same in the most recent survey (Mercer et al, 1996). The linkage between authoritative definitions and federal and state regulations defining MR and LD are fairly evident as most states have modeled their definitions and criteria after those suggested in authoritative definitions.…”
Section: Focus On Exceptional Children October 1997mentioning
confidence: 99%
“…That definition reads: "Mental retardation refers to significantly subaverage general intellectual functioning existing concurrently with deficits in adaptive behavior, and manifested during the developmental period" (Grossman, 1973, p. 5). The authoritative definition produced by the NACHC (1968) was adopted in the federal regulations authored by the U.S. Office of Education (1977), defining LD (Mercer, Jordan, Allsopp, & Mercer, 1996). That definition reads:…”
Section: Influence Of Authoritative Definitions On Federal and State mentioning
confidence: 99%
“…E-Mail: mdwairy@construct.haifa.ac.il mentioned very frequently (Katz & Slomka, 2000). Despite the increased criticism of this discrepancy criterion, it is still included in the definition and/or criteria of 98% of the states in the USA (Mercer, Jordan, Allsopp, & Mercer, 1996).Inherent in most of the conceptualization of LD is the potential for at least average intellectual functioning while academic performance is well below grade or age expectations. This low academic performance is due, typically, to a deficiency in some specific cognitive functions that are needed for learning.…”
mentioning
confidence: 99%